Analisis Nilai Keekonomian Ketersediaan Kebutuhan Alat Penunjang Tambang untuk Operasional Pengupasan Overburden Dalam Meningkatkan Produktivitas Shovel PC3000E-6 - Maya Matofani; Edwin Harsiga; Ayu Srimarta (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2023)
Pit 3East ElectrificationBanko Barat PT Bukit Asam, tbk has provided mining support equipment of 2 units of Komatsu D375A bulldozer, 4 units of Komatsu D85SS bulldozer, 1 unit of MG825 grader and 1 unit compactor, with rental status. However, the availability of supporting equipment that has been provided can not fully support the April 2018 production target Therefore it is necessary to recalculate the amount of supporting equipment that should be provided in April 2018. After the improvement efforts in the form of additional supporting equipment, the total production capable of producing PC3000E-6 shovel amounted to 729,932 bcm / month, an increase of production amounted to 329,535 bcm / month.The result of calculation of requirement of mine supporting tool based on productivity of each tool can be concluded that the number of tools that should be provided are 2 units of Komatsu D375A bulldozer, 5 bulldozer D85SS units, 3 MG825A grader units and 2 compactor units. Based on calculations made the company issued a rental fee lower than the actual APT rental fee of Rp7.769 / bcm which is Rp 5,919 / bcm, making it more profitable than the previous conditions.